Ethnic diversity matters: Putting implicit associations between weapons and ethnicity in context. (February 2020) - Sadler, Melody; Devos, Thierry
Weapons are implicitly associated with Black Americans. We examined the extent to which this implicit stereotype fluctuates as a function of the ethnic diversity of contexts. Across 351 U.S. metropolitan areas, we tested whether three distinct indicators of ethnic diversity predicted implicit associations between the concept of "weapons" (vs. "harmless objects") and Black Americans vs. White Americans. As predicted, implicit Black–weapon stereotypes were weaker in areas characterized by the presence of multiple ethnic groups (variety) and greater dispersion of ethnic groups at the neighborhood level (integration). Additionally, the negative association between integration and implicit stereotypes was strongest when minority representation was low compared to high. Considering multiple dimensions of ethnic diversity proved useful to document reliable relations between implicit associations and characteristics of local contexts.